Policewoman, social welfare worker, guard: Female culpability during National Socialism (KULT_online, 2010)
Which roles did women play in the national socialist dictatorship? This question is posed by the author of the present study, and she answers it, following current insights in the field, by identifying women as actors and perpetrators. One of Kathrin Kompisch's theses is that woman in the 'Third Reich' had a much wider sphere of influence than one wanted to admit in the aftermath of the war. They were not only part of administration and economy: in women's organizations such as the Nationalsozialistische Frauenschaft or the Bund Deutscher Mädel, they assumed leading functions and thus had direct influences. They were also present everywhere in the terror apparatus of the regime: as office employees they typed reports about mass executions for the SS, as custodians they guarded female inmates of the concentration camps, as secretaries they took minutes of questionings under torture. Historian Kompisch in her book treats these and many other areas in detailed ways and shows that the female part of the population not only knew of the crimes against humanity, but they took part actively in them.